Related and unrelated diversification strategy on performance / Wan Mohd Nazri Wan Daud - Wan Daud, Wan Mohd Nazri (2014)
Diversification strategy has been debated in the fields of strategic management and finance. Inconclusive evidences pertaining to the effect of diversification strategy and debt on performance prevail in developed countries. Some studies suggest doing empirical research in developing countries to search for fresh evidence to validate those claims. This study examines the effect of diversification and debt usage on performance. Multiple proxies of performance are used namely market, economic, risk adjusted and accounting measurements in order to select the best proxy to explain the relationship among variables. The method deployed is panel data analysis on a sample of 76 Malaysian firms from various industries for the period of 1994 to 2007. These firms were then classified into 32 related firms and 44 unrelated firms based on type of diversification adopted. Independent variables such as cash flow, capital expenditure, liquidity and size were employed to provide robust evidence pertaining to the relationship between diversification, debt and performance. In addition to using the whole sample, the study also divides it into two periods: pre- and post-crisis. In determining the relationship among variables, multiple regressions were used. The results for all samples do not support the view that debt can be used to enhance performance once the unrelated diversification strategy is implemented. Similarly, debt also is not a factor that can be used to enhance performance in related diversified firms. The results remain consistent for the pre- and post-crisis periods where no significant relationship exists between diversification strategy and performance. The evidence suggests that debt clearly has a negative impact on performance. Therefore, firms should put extra caution in using debt as their financing choice. Apart from that, firms should also monitor other factors that may have a significant impact on performance such as cash flow. Future studies should explore international diversification strategy to investigate whether debt could enhance performance once unrelated strategy has lowered firm’s business risk.